A Review of 'Nutrition and Feeding of Organic Poultry 2nd Edition' - Werner J. Zollitsch (Organic Farming, 2018)
"Nutrition and Feeding of Organic Poultry" is a reference book for producers, advisory personnel, teachers, students and technical experts who are searching for sound information on the basics of nutrition, feed characteristics, practical diet formulation and the impact of nutrition on productivity, health and welfare of organic poultry.